2002
DOI: 10.1128/jb.184.5.1462-1465.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Myxococcus xanthus Social Motility dsp Mutations to the dif Genes

Abstract: Myxococcus xanthus dsp and dif mutants have similar phenotypes in that they are deficient in social motility and fruiting body development. We compared the two loci by genetic mapping, complementation with a cosmid clone, DNA sequencing, and gene disruption and found that 16 of the 18 dsp alleles map to the dif genes. Another dsp allele contains a mutation in the sglK gene. About 36.6 kb around the dsp-dif locus was sequenced and annotated, and 50% of the genes are novel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…DifA was previously predicted to be a 43.5-kDa protein with an ATG start codon ( Fig. 1A) (10,17,29,48). However, its apparent molecular mass is about 50 kDa, as estimated by SDS-PAGE and immunoblotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DifA was previously predicted to be a 43.5-kDa protein with an ATG start codon ( Fig. 1A) (10,17,29,48). However, its apparent molecular mass is about 50 kDa, as estimated by SDS-PAGE and immunoblotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the signaling mechanism utilized by DifA is not well understood, especially in regard to EPS regulation. Previous bioinformatics analysis predicted that DifA starts immediately with its first transmembrane helix (TM1), which is followed by a 10-residue periplasmic region, the second TM helix (TM2), and the cytoplasmic signaling domain (29,48). The lack of an obvious signal sensory domain, whether at the cytoplasmic N terminus or in the periplasm, was perplexing.…”
mentioning
confidence: 99%
“…The PPK1 mutant, which is strikingly defective in S-motility, accumulates an excessive amount of the cell-surface pilin; this hyperpiliation phenotype is likely due to an insufficient amount of fibril EPS (27) and perhaps other fibril components. Biogenesis of EPS involves genes eps and eas (35), a DnaK homolog (encoded by sglK) (36), chemotaxis homologues (dif ) genes (37), and some uncharacterized dsp genes. EPS-deficient mutants fail to bind calcofluor white dye (38) and are defective in cellular agglutination, S-motility, and fruiting body formation (25,26), phenotypes similar to those in the PPK1 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…2, Right). To eliminate the possibility that stimulation was caused by extracellular complementation of exopolysaccharide (EPS) molecules, we tested whether a dsp/dif mutant, which is defective in EPS production (25,26), could be stimulated for motility. Using the same procedure, we observed that motility was not stimulated in this strain (Fig.…”
Section: Ome Rescues the Motility And Development Of O-antigen Mutantsmentioning
confidence: 99%